Pengaruh Faktor Fundamental Terhadap Return Saham Syariah Pada Perusahaan Di Bursa Efek Indonesia Yang Tergabung Dalam Jakarta Islamic Index - Eli Achmad Mahiri (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2020)
This study aims to determine the effect of fundamental factors (EPS), Return on Equity (ROE) and Debt to Equity Ratio (DER) on Stock Returns in Islamic stock companies incorporated in the Jakarta Islamic Index (JII) which are listed in Indonenisa Stock Exchange. The research method used is a survey method with descriptive and verification approaches. The test instruments used in this study are validity and reliability tests. The data analysis used in this research is the classical assumption test, multiple regression analysis, the coefficient of determination, and hypothesis testing. Based on the results of the study, it shows that the variable Earning Per Share has no effect on the stock returns of companies incorporated in the Jakarta Islamic Index, the Return On Equity variable has a significant positive effect on the stock returns of companies incorporated in the Jakarta Islamic Index. The Debt to Equity Ratio variable has a significant negative effect. to the stock returns of companies incorporated in the Jakarta Islamic Index ..